2012
DOI: 10.2118/139668-pa
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Mechanistic Model To Forecast Cement-Sheath Integrity

Abstract: Summary Tests performed in the laboratory have shown that there exist two types of mechanisms that could lead to loss of cement-sheath integrity: mechanical degradation, when cement is submitted to compressive or tensile loadings that are too high compared with its strength, and chemical degradation. The worst case is when both mechanisms occur at the same time or one after the other. For example, a cement sheath that is damaged before entering into contact with a degrading fluid will allow this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(36 citation statements)
references
References 14 publications
2
34
0
Order By: Relevance
“…Carpenter et al (1992) found that thermal cycling is destructive to the cement/casing bond for various cement types, and that just a single thermal cycle with an amplitude of 56 C could damage the bond. Similar trends, displaying that both pressure and temperature variations aggravate the casing/cement bond, were observed by Boukhelifa et al (2004) and Bois et al (2012). Detailed experimental studies of annular-cement debonding and cracking were also recently performed by Albawi et al (2014) andDe Andrade et al (2014).…”
Section: Introductionsupporting
confidence: 67%
“…Carpenter et al (1992) found that thermal cycling is destructive to the cement/casing bond for various cement types, and that just a single thermal cycle with an amplitude of 56 C could damage the bond. Similar trends, displaying that both pressure and temperature variations aggravate the casing/cement bond, were observed by Boukhelifa et al (2004) and Bois et al (2012). Detailed experimental studies of annular-cement debonding and cracking were also recently performed by Albawi et al (2014) andDe Andrade et al (2014).…”
Section: Introductionsupporting
confidence: 67%
“…Uniform tensile stress (p) was load at the surface of crack. The stress intensity factor 3 K p a π = . When the cracks propagate along with the second interface, the self-strength (σ s ) of interface should be overcomed.…”
Section: The Calculation Of Stress Intensity Factor (K I ) At the Peamentioning
confidence: 99%
“…The type of completion is casing perforation. The designed amount of silica sand was 175.8m 3 , and artificial haydite was 40m 3 . Total liquid volume is 1795m 3 .…”
Section: Case Studymentioning
confidence: 99%
“…As described in the previous section, cement sheaths typically fail because of volumetric instability and imposed tensile stresses beyond the tensile strength of the cement sheath. (Shadravan et al, 2014;Williams et al, 2011) Pressure increase is more damaging because the fluid injection lasts from minutes to hours (Thiercelin et al, 1998) Several have suggested requirements to tensile strength, Young's modulus, and other mechanical properties of the cement sheath to provide a long-term zonal isolation through long-term stress evaluation (Bois et al, 2011;Bois et al, 2012;Roy-Delage et al, 2000;Saint-Marc et al, 2008;Stiles and Hollies, 2002). Thiercelin et al (1998) analyzed different stress conditions in oil wells which were applicable for most types of loading.…”
Section: Requirements To Cement Systems To Provide Long-term Zonal Ismentioning
confidence: 99%